رفع الأداء الوظيفي للمورد البشري من المنظور القيمي الإسلامي: Raising the performance of human resources from the Islamic values perspective - Hakima, Merazga; Achour, Meguellatti; Sarif, Suhaili (Online Journal of Research in Islamic Studies, 2020)
The human resource is the pulse of any organization of any kind, and the performance of the human resource is the artery of the institution and its effectiveness. The performance of any human resource is measured by the extent of its achievement and achievement of the goals. Among the factors that lead to higher performance are the human values, performance and human resource. This study comes to answer the main question: How do Islamic values â€‹â€‹contribute to raising the human resource’s performance? The study will lead to a number of objectives, including a better understanding of the concept of job performance, the diagnosis of Islamic values, and the discovery of the contribution of Islamic values, especially administrative ones, to the performance of the human resource. This will be done according to the methodology of description, mainly in the performance of the function and Islamic values, as a central study of this study detailing how the contribution of Islamic values â€‹â€‹in raising the functionality of the human resource.